Analisis Leverage Dalam Mengukur Risiko Studi Kasus Pada PT. Pabrik Kertas Tjiwi Kimia Tbk - Andi Amri (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2021)
The purpose of this study is to look at the risk of PT. Tjiwi Kimia Tbk Paper Plant in terms of business risks, financial risks, and total risk caused by looking at specific problems within the company to obtain various measures that are useful for measuring risk levels. Form of research that uses observation by using descriptive analysis method to describe course of an ongoing research or looking for problems that occur in the company where the author wakes up research. Result of research: 1). Operating Leverage (DOL) for the last six years has not been good, because the resulting DOL tends to increase this meaning the company has not been able to reduce its business risk. 2) The resulting Financial Leverage (DFL) contains a downward trend which can be seen from the decrease in EPS generated so that the company has not been able to reduce its financial risk. 3) Total Leverage (DTL) generated can still change, with DTL result every year tends to increase and decrease (inconsistent) seen from variation of EPS produced every time following sales up and down. PT. Tjiwi Kimia Tbk Paper Plant can reduce the total risk if it can drop DOL and increase DFL.